Quantity, quality and physical protection of soil carbon associated with sugarcane straw removal in southern Brazil - Pimentel, Marcelo Laranjeira [UNESP]; de Oliveira, Aline Barbosa [UNESP]; Schiebelbein, Bruna Emanuele; Carvalho, Martha Lustosa; Tenelli, Sarah; Cherubin, Maurício Roberto; Carvalho, João Luís Nunes; Briedis, Clever; Panosso, Alan Rodrigo [UNESP]; de Oliveira Bordonal, Ricardo (Elsevier, 2024)
Sugarcane straw is identified as a potential energy feedstock to increase bioenergy production, but advances are required in understanding the straw removal impacts on soil organic carbon (SOC) stability and storage. The main objective of this study was to evaluate the quantity, quality and physical protection of SOC under areas with different straw removal rates over a six-year period. A field experiment was conducted in randomized blocks with four replications, including the following straw removal treatments: total removal (TR), high removal (HR), low removal (LR), and no removal (NR), corresponding to the quantities of 0, 5, 10 and 15 Mg ha−1 of dry straw maintained on soil surface, respectively. Effects of straw removal on SOC stocks and its temporal dynamics, as well as the rates of carbon (C) incorporated into the soil were evaluated to a 0.3-m depth. The effects on particulate organic matter (POM) and mineral-associated organic matter (MAOM) fractions were evaluated through physical fractionation of SOM. Finally, it was evaluated the distribution of aggregates, the C content of aggregates and the C preservation capacity (CPC) in fractions of aggregates. Our findings revealed that TR and HR decreased SOC stocks at 0.0–0.1 m and 0.0–0.3 m depths. The data indicated that about 24% of the C added via straw were retained in soil, and NR showed a SOC accumulation rate of 1.42 Mg ha-¹ year-¹ relative to baseline. Low straw removal increased POM (46.2%) and MAOM (12.4%) in surface layer as compared to TR. The straw maintenance in the field increased the proportion of soil macroaggregates, resulting in higher amounts of C preserved in this fraction. Our findings suggest that maintaining 10 Mg ha-¹ of straw was enough to favor physical protection and sustain storage of SOC over time. Therefore, the surplus of straw could be removed to produce bioenergy, although this management may hinder soil C sequestration and its benefits for sugarcane production and climate change mitigation.
Keywords: Carbon stabilization; Crop residues; Mineral-associated organic matter; Particulate organic matter; Soil aggregation; Soil health